Prophetic business ethics - Musa, Muhammad Adli (IIUM Press, International Islamic University Malaysia, 2017)
This study will concentrate on categorising and analysing selected aḥādīth, found in al-Kutub al-Sittah (The Six [Major] Books [of Ḥadīth]: Ṣaḥīḥ al-Bukhārī, Ṣaḥiḥ Muslim, Sunan Abī Dāwud, Sunan al-Tirmidhī, Sunan al-Nasā´ī al-Mujtabā and Sunan Ibn Mājah) along with al -Mustadrak Ñalā al-Ṣaḥīḥayn by al-Ḥākim to identify what is considered ethical and unethical in the conduct of business transactions.